Indentation Response and Structure‐Property Correlation in a Bimodal Ti–6Al–4V Alloy. Issue 12 (14th August 2017) - Sen, Indrani; Roy, Shibayan; Wagner, Martin F.‐X.
Abstract : Understanding the deformation behavior of multi‐ phase alloys under external loading requires careful mechanical characterization of the individual constituent phases at various length scales. The present study first evaluates the elastic moduli and hardness of the microstructural constituents viz. primary α ( α p ) and transformed β (secondary α ( α s ) plus retained prior β ) phases in a bimodal Ti–6Al–4V alloy by nano‐ indentation using different loads. The bulk mechanical properties of the overall microstructure are then determined by grid wise nano‐ indentation, as well as micro‐ indentation. The alloy shows a pronounced indentation size effect; the hardness increases with the decrease in indentation load, or depth of penetration. Assuming an iso‐ stress condition for individual constituents ( α p and transformed β ) in the rule of mixture approach, the bulk mechanical properties of the Ti–6Al–4V alloy are reasonably predicted. Such prediction of bulk properties, however, is not possible when a similar calculation is performed using iso‐ strain condition. The transformed β phase shows disparity between the estimated and experimental values, while considering the α s and β phases individually, on both iso‐ stress and iso‐ strain assumptions. From these results, the influence of individual microstructural phases (size, distribution, volume fraction, morphology) and the interfaces between them, is found key in controlling the overall bulk mechanical response of the alloy system. Abstract : The study evaluates mechanical properties of microstructural constituents in a bimodal Ti–6Al–4V alloy by nano‐ and micro‐indentation. The role of size, distribution, morphology, volume fraction, and interfaces of these constituents in controlling the bulk mechanical response is rationalized by a rule of mixture based theoretical calculation.